Periadventitial β-aminopropionitrile-loaded nanofibers reduce fibrosis and improve arteriovenous fistula remodeling in rats - Applewhite, Brandon; Gupta, Aavni; Wei, Yuntao; Yang, Xiaofeng; Martinez, Laisel; Rojas, Miguel G.; Andreopoulos, Fotios; Vazquez-Padron, Roberto I. (Frontiers in Cardiovascular Medicine, 2023)
Background Arteriovenous fistula (AVF) postoperative stenosis is a persistent healthcare problem for hemodialysis patients. We have previously demonstrated that fibrotic remodeling contributes to AVF nonmaturation and lysyl oxidase (LOX) is upregulated in failed AVFs compared to matured. Herein, we developed a nanofiber scaffold for the periadventitial delivery of β-aminoproprionitrile (BAPN) to determine whether unidirectional periadventitial LOX inhibition is a suitable strategy to promote adaptive AVF remodeling in a rat model of AVF remodeling. Methods Bilayer poly (lactic acid) ([PLA)-]- poly (lactic-co-glycolic acid) ([PLGA)] scaffolds were fabricated with using a two-step electrospinning process to confer directionality. BAPN-loaded and vehicle control scaffolds were wrapped around the venous limb of a rat femoral-epigastric AVF during surgery. AVF patency and lumen diameter were followed monitored using Doppler ultrasound surveillance and flow was measured before euthanasia. AVFs were harvested after 21 days for histomorphometry and immunohistochemistry. AVF compliance was measured using pressure myography. RNA from AVF veins was sequenced to analyze changes in gene expression due to LOX inhibition. Results Bilayer periadventitial nanofiber scaffolds extended BAPN release compared to the monolayer design (p<0.005) and only released BAPN in one direction. Periadventitial LOX inhibition led to significant increases in AVF dilation and flow after 21 days. Histologically, BAPN trended toward increased lumen and significantly reduced fibrosis compared to control scaffolds (p<0.01). Periadventitial BAPN reduced downregulated markers associated with myofibroblast differentiation including SMA, FSP-1, LOX, and TGF-β while increasing the contractile marker MYH11. RNA sequencing revealed differential expression of matrisome genes. Conclusions Periadventitial BAPN treatment reduces fibrosis and promotes AVF compliance. Interestingly, the inhibition of LOX leads to increased accumulation of contractile VSMC while reducing myofibroblast-like cells. Periadventitial LOX inhibition alters the matrisome to improve AVF vascular remodeling.